A Look at Latin American Epistemology and Pedagogical Mediation in the Teaching of Science in General - Mesén Mora, Luis Diego (2021)
The critical analysis of traditional and Latin American epistemology allows building a frame of reference that helps to understand the current educational situation. The marked globalization trend in the teaching and learning processes has helped to increase the social gap since colonial times. The development of autochthonous culture permits the creation of a Latin American conscience that allows basing the educational processes on the traditions and not on the imposed Western epistemology. In this way, critical and emancipatory pedagogy allows us to design a learning process that fosters the development of social, cultural, and scientific skills that support the evolution of the country. With this epistemological basis, it is possible to work with a critical didactics in the teaching of science that allows opening new models of pedagogical mediation, achieving a comprehensive and equitable education.